(untitled) (American Journal of Islam and Society, 1999)
To what extent is some poverty necessary for economic growth? Does poverty motivate the poor to work harder, enabling them to both escape their poverty and in the process increase the total wealth of society? Or does poverty on balance promote those negative influences such as ill-health and a lack of proper education that prevent the poor, and hence society, from attaining its full wealth potential? What effect does a redistribution of wealth from rich to poor have upon the growth rate? Would the poor manage the extra wealth thereby gained in a manner more beneficial for society than when the rich managed it? How does income disparity within an economy wax and wane as growth takes place, and how does income disparity between economies change in the face of globalization? Perhaps most important of all, what can political economists learn from past experiences in informing policy recommendations for the future? Such are the questions to which two professors of economics address in Growth, Inequality and Globalization: Theory, History, and Policy. In the first of two discussions on the topic, phillipe Aghion from University College London adopts a largely mathematical approach. In the second discussion, Jeffery G. Williamson from Harvard undertakes an empirical analysis. These two approaches compliment one another rather well. Two ideas are generally handed down to the modem student of economics on the relationship between growth and wealth inequality. One is based upon an incentives theory according to which inequality promotes faster growth. The other derives from the Kuznet’s hypothesis which holds that, as an economy passes through a growth phase, inequality first increases and then decreases with the onset of maturity. Aghion labels both of these ideas as fallacies, briefly citing recent evidence which shows widening income inequality in the United States. His mathematical modeling further shows that, under certain circumstances, increases in inequality (as measured by the increased dispersion of investment holdings among members of the society) can lead to lower growth. This is because the marginal return on investment for the poor is greater than for the rich. In plain language, poor people can create more wealth with an additional unit of investment assets than the rich can. Hence, if the rich have all the assets, society as a whole may not achieve the highest available returns. In a perfect capital market, the rich could perhaps lend or invest their surplus ...